Liver stiffness‐spleen size‐to‐platelet ratio risk score identifies esophageal varices in Japanese patients with chronic hepatitis C. Issue 9 (11th January 2016) - Shibata, Soichiro; Umemura, Takeji; Yamazaki, Tomoo; Fujimori, Naoyuki; Ichikawa, Yuki; Kimura, Takefumi; Joshita, Satoru; Komatsu, Michiharu; Matsumoto, Akihiro; Tanaka, Eiji
Abstract: Aim: Non‐invasive methods are needed to identify esophageal varices (EV) in patients with chronic liver disease. To this end, we evaluated liver stiffness (LS)‐spleen diameter‐to‐platelet ratio risk score (LSPS) in predicting EV among Japanese chronic hepatitis C patients. Methods: A total of 99 patients with chronic hepatitis C who had undergone endoscopy, LS measurement and ultrasonography between 2013 and 2014 were enrolled. Clinical data were compared with those for other non‐invasive markers (platelet count, aspartate aminotransferase‐to‐platelet ratio, FIB‐4 index and platelet‐to‐spleen ratio), spleen size, LS and controlled attenuation parameter. Diagnostic applicability was assessed by the area under the receiver–operator curve (AUC) and predictive values along with multivariate logistic regression. Results: LSPS was significantly correlated to the grade of EV (ρ = 0.617, P  < 0.001) and was superior to the other non‐invasive indices for determination of EV. LSPS was independently associated with EV by multivariate logistic regression analysis (odds ratio, 3.079; 95% confidence interval [CI], 2.137–4.438; P  < 0.001). The cut‐off value of LSPS for EV was 0.7, for which the AUC, sensitivity, specificity, positive predictive value, negative predictive value and accuracy were 0.928 (95% CI, 0.876–0.980), 86.3%, 89.6%, 70.4%, 95.8% and 88.9%, respectively. Conclusion: LSPS may also identify EV in patients with chronic hepatitis C in Japan. The clinical values of LSPS for EV risk merit further validation in larger prospective studies.